Damned nation: hell in America from the Revolution to Reconstruction - Gin Lum, Kathryn ca. 20./21. Jh. (Oxford University Press, 2014)
Hell mattered in the United States' first century of nationhood. The fear of fire-and-brimstone haunted Americans and shaped how they thought about and interacted with each other and the rest of the world. 'Damned Nation' asks how and why that fear survived Enlightenment critiques that diminished its importance elsewhere.